Revision of the Oriental genus Holophris Mocsáry, 1890 and description of the genus Leptopareia Rosa & Xu, gen. nov. (Hymenoptera, Chrysididae) - Rosa, Paolo; Wei, Na-Sen; Notton, David; Xu, Zai-Fu (Zootaxa, 2016)
Two Oriental genera of the tribe Elampini (Chrysidinae) are here discussed. The genus Holophris Mocsáry, 1890 is redescribed, and the genus Leptopareia Rosa & Xu, gen. nov. (type species Hedychrum borneanum Cameron, 1908) is established. Two new species are described: Holophris thailandica Rosa, Wei, Notton & Xu, sp. nov. (Thailand), and Leptopareia luzonensis Rosa, Wei, Notton & Xu, sp. nov. (Philippines, Luzon). The lectotype of Hedychrum borneanum Cameron, 1908 is designated. New combinations are proposed for L. borneana (Cameron, 1908), comb. nov., L. purpurea (Smith, 1860), comb. nov., L. abyssinica (Mocsáry, 1914), comb. nov., L. confusa (Kimsey, 1988), comb. nov., L. congoensis (du Buysson, 1900), comb. nov., and L. kalliopsis (Zimmermann, 1961), comb. nov. (all are from Holophris Mocsáry). Holophris marginella (Mocsáry, 1890) is newly recorded from China and Thailand; H. taiwana (Tsuneki, 1970) from India, Indonesia and Laos; and Leptopareia borneana (Cameron, 1908) from Thailand. Keys to Oriental genera of the tribe Elampini and to Oriental species of the two genera are provided.